2019
DOI: 10.1088/1755-1315/393/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

The exploration and utilization of functional microorganisms isolated from the tropical peatlands

Abstract: The utilization of peatlands may decline the ecological functions of peatlands as carbon sink, water storage and biodiversity source. Therefore, different scientific approaches are required to increase peat productivity and inhibit decline in the ecological functions of peatlands. This article is aimed to provide information on researches that have been carried out in tropical peats in the South Kalimantan Province. The exploration and the potential utilization of microbes was reviewed from several studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Biofertilizers significantly increased the total N and pH of the peat but did not significantly reduce the C/N ratio of the peat. The results of the study (26) concluded that the use of functional microorganisms is an alternative to peatland management for agricultural practices. Improvement of peat soil properties with the application of ameliorant followed by fertilization with either one or a combination of NPK fertilizer, peat fertilizer (pugam), or biological fertilizer has the potential to increase onion productivity which is higher than the national average productivity >9.31 t ha -1 (27).…”
Section: Resultsmentioning
confidence: 96%
“…Biofertilizers significantly increased the total N and pH of the peat but did not significantly reduce the C/N ratio of the peat. The results of the study (26) concluded that the use of functional microorganisms is an alternative to peatland management for agricultural practices. Improvement of peat soil properties with the application of ameliorant followed by fertilization with either one or a combination of NPK fertilizer, peat fertilizer (pugam), or biological fertilizer has the potential to increase onion productivity which is higher than the national average productivity >9.31 t ha -1 (27).…”
Section: Resultsmentioning
confidence: 96%